Enhancing Millennial Performance Through Anti-Fraud Strategies: Integrating Deviant Behavior, Work Commitment, and Maqasid Al-Shariah Values - Deden Kurniawan; Abdul Aziz; Andini Ayu Larasati; Sugeng Priyanto; Abdul Hakim (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2025)
Examining millennials' views on Indonesia’s ideal future highlights ways to rebuild their trust in democracy and shows their strong rejection of corrupt behavior. This study examines the anti-fraud strategies as a mediating variable and implementation of maqashid al-syariah on millennial employee performance at PT Permodalan Nasional Madani (PNM). Employing a mixed-methods design, quantitative data were obtained from 140 purposively sampled millennial employees and analyzed using SEM-PLS version 4.0. The qualitative phase utilized semi-structured interviews, analyzed thematically within the normative framework of Maqasid al-Shariah to contextualize ethical considerations. The variables assessed include deviant workplace behavior, work commitment, anti-fraud strategy implementation, and employee performance. Findings demonstrate that deviant workplace behavior negatively and significantly affects both anti-fraud strategy implementation and employee performance, whereas work commitment exerts a positive and significant influence. Additionally, anti-fraud strategies function as a significant mediator in these relationships. The study contributes theoretically by integrating Maqasid al-Shariah principles as a culturally grounded ethical lens for understanding millennial workplace conduct, emphasizing values of amanah (trust) and adl (justice) in mitigating deviance and fostering commitment. The qualitative insights corroborate the quantitative results, underscoring the role of Islamic ethics in reinforcing organizational integrity. This study shows that strong work commitment improves millennial performance and supports anti-fraud efforts, while deviant behavior harms both. Anti-fraud strategies reduce negative behavior and strengthen commitment. Using Maqasid al-Shariah values helps build ethical, trustworthy, and effective organizations.